Detection and characterization of cloud enhancement events for solar irradiance using a model-independent, statistically-driven approach. (October 2020) - Castillejo-Cuberos, Armando; Escobar, Rodrigo
Highlights: Several cloud enhancement event definitions compared. A novel model-independent, statistically driven detection framework is proposed. Cloud enhancement events are quantified, described and analized at eight locations. Results contextualized against maximum expected clear sky irradiances. Record irradiance values for thermopile and photodiode sensors are reported. Abstract: Cloud enhancement events are instances in which the cloud pattern increases global horizontal irradiance on the ground above levels higher than would otherwise be expected during clear sky with cloudless conditions, and in general, these events are characterized by high irradiances occurring during highly changing transient conditions. Even though it is a well-known although infrequent phenomenon, currently no consensus exists as to its formal definition. However, several studies point out to a need for a better understanding of this phenomenon due to their effects on mathematical models or photovoltaic systems behavior during these instances, as results show significant deviations with respect to the expected results in normal conditions. Due to these issues, the present work intends to explore cloud enhancement definitions and detection methods, for which a novel model-independent, statistically-driven approach is proposed and compared to three other models found in the literature. Assessments are made regarding the main aspects of the phenomenon: frequency of occurrence, clearness index, diffuse fraction and its relationship with solar resource variability. Data from eight measurements sites throughout Chile, with different climatic characteristics is used. To further support the analysis made, monthly maximum expected clear sky irradiance for each site was estimated through satellite-based data as well as with estimation from ground measurements. Finally, the highest irradiances are presented for each measurement site reporting, the record irradiances for one-minute data thermopile and photodiode pyranometers.